Thyroglossal cyst malignancy: Two cases of exception - da Costa, Liliana Filipa Invencio; de la Iglesia, Francisco Vázquez; González-Botas, J. Jesús Herranz (Revista Portuguesa de Otorrinolaringologia-Cirurgia de Cabeça e Pescoço, 2020)
Introduction: the thyroglossal duct cyst (TDC) is the most common congenital malformation in the neck. It is usually a benign tumor, but can suffer malignant transformation. The majority of cases of TDC occur in childhood; its diagnosis in adult patients is unusual. Clinical case: we present two clinical cases of malignant QT. Discussion: most of the TDC carcinomas are diagnosed incidentally. However, a rapid growth, changes in TDC characteristics, and findings in complementary imaging exams of calcification, nodules, and irregular margins should alert to a possible malignization. There is no consensus regarding the need for additional treatments to the Sistrunk procedure, such as total thyroidectomy with or without neck dissection, radioactive iodine therapy or hormone suppression. However, the decision must not forget the patient’s functional status with the aim of avoiding high morbidity and mortality.